Aminoclay Nanoparticles Induce Anti-Inflammatory Dendritic Cells to Attenuate LPS-Elicited Pro-Inflammatory Immune Responses - Hyun Jung Park; Sung Won Lee; Jae Geun Song; Luc Van Kaer; Jae Hee Cheon; Soo-Jeong Lim; Hyo-Kyung Han; Seokmann Hong (Molecules, 2022)
Although 3-aminopropyl functionalized magnesium phyllosilicate nanoparticles (hereafter aminoclay nanoparticles, ACNs) are well-known nanomaterials employed as drug carriers, their effects on immune cells remain unclear. To address this issue, we explored murine dendritic cells (DCs) as these cells belong to the innate arm of the immune system and function as antigen-presenting cells to elicit adaptive immune responses. We examined the in vitro effects of ACNs on DCs isolated from B6 mice. ACN treatment significantly down-regulated the expression of inflammasome-related markers, including NLRP3, caspase-1, and IL1β. The ACNs-induced anti-inflammatory DC phenotype was further confirmed by down-regulation of the AKT/mTOR/HIF1α signaling pathway. Such anti-inflammatory effects of ACNs on DCs occurred independently of DC subtypes. To document the effects of ACNs on DCs more clearly, we examined their anti-inflammatory effects on lipopolysaccharide (LPS)-activated DCs. As expected, excessive inflammatory responses (increased mitochondrial ROS and Th1-type cytokines such as IL12 and IL1β) of LPS-activated DCs were dramatically attenuated by ACN treatment. Furthermore, ACNs down-regulated IFNγ production by antigen-specific CD4+ T cells, which is consistent with a reduced inflammatory phenotype of DCs. Overall, our results provide support for employing ACNs as drug delivery materials with therapeutic potential to control inflammatory disorders.